Effects of Combined Physical and Cognitive Virtual Reality-Based Training on Cognitive Impairment and Oxidative Stress in MCI Patients: A Pilot Study - Mrakic-Sposta, Simona; Di Santo, Simona G.; Franchini, Flaminia; Arlati, Sara; Zangiacomi, Andrea; Greci, Luca; Moretti, Sarah; Jesuthasan, Nithiya; Marzorati, Mauro; Rizzo, Giovanna; Sacco, Marco; Vezzoli, Alessandra (Frontiers in Aging Neuroscience, 2018)
There is a pressing demand for improving the quality and efficacy of health care and social support services needed by the world’s growing elderly population, especially by those affected by mild cognitive impairment (MCI) and Alzheimer’s disease. Exercise has been demonstrated to mitigate cognitive impairment and oxidative stress (OxS) that has been recognized as a contributing factor in the progression of multiple neurodegenerative diseases. Meeting the demand of innovative and addressed to specific needs treatment in the area of cognitive impairment mitigation and rehabilitation, the main objective of this pilot study was to evaluate the impact of a Virtual Reality-based programme combining aerobic exercise and cognitive training. 10 patients (aged 73.3 ± 5.7 ys) with MCI (Mini-Mental State Examination, MMSE: 23.0 ± 3.4) were randomly assigned to either 6 weeks physical and cognitive training (EXP) or control (CTR) group. Evaluations of cognitive proﬁle, by a neuropsychological tests battery, and OxS, by collection of blood and urine samples, were performed before and at the end of the experimental period. Also the assessment of the patients’ opinions toward the intervention was investigated through questionnaires. EXP group showed a tendency towards improvements in the MMSE, in visual-constructive test and visuo-spatial tests of attention, while the controls worsened. EXP group had a greater improvement than CTR in the executive test, memory functions and verbal ﬂuency. None of the comparisons within and between groups reached statistical signiﬁcance, reasonably due to small sample, which amplifies the effect of the slight heterogeneity in scores between subjects. Despite, a greater worsening of Activities of Daily Living (ADL) tests, all participants reported a better performance in real life thanks to the self-perceived improvement elicited. After training intervention OxS (i.e reactive oxygen species production, oxidative damage of lipids and DNA) decreased resulting significantly (range P<0.05-0.001) lower in EXP vs CTR group. Although not conclusive, the recorded effects in the present study are promising and suggest that this proposed would be an useful tool in support of cognitive training reducing oxidative stress too. Further studies on larger samples of patients are needed.